2010
DOI: 10.1370/afm.1159
|View full text |Cite
|
Sign up to set email alerts
|

Using Learning Teams for Reflective Adaptation (ULTRA): Insights From a Team-Based Change Management Strategy in Primary Care

Abstract: PURPOSEThe Using Learning Teams for Refl ective Adaptation (ULTRA) study used facilitated refl ective adaptive process (RAP) teams to enhance communication and decision making in hopes of improving adherence to multiple clinical guidelines; however, the study failed to show signifi cant clinical improvements. The purpose of this study was to examine qualitative data from 25 intervention practices to understand how they engaged in a team-based collaborative change management strategy and the types of issues the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 34 publications
(39 reference statements)
1
81
0
Order By: Relevance
“…This may help explain why RAP practices with higher Change Culture scores had less improvement. Congruent with our findings, another study using the RAP approach to improve adherence to clinical guidelines in 25 primary care practices reported that successful RAP teams often initially addressed "unacknowledged tensions," a process that resulted in improved communication in 12 practices, 26 although primary outcomes did not improve significantly. 44 A more focused and structured approach (with tailoring for individual practice culture, circumstances, and needs)-at least over the duration of our project-produced stronger improvement in diabetes quality measures than a less structured and more open-ended approach.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This may help explain why RAP practices with higher Change Culture scores had less improvement. Congruent with our findings, another study using the RAP approach to improve adherence to clinical guidelines in 25 primary care practices reported that successful RAP teams often initially addressed "unacknowledged tensions," a process that resulted in improved communication in 12 practices, 26 although primary outcomes did not improve significantly. 44 A more focused and structured approach (with tailoring for individual practice culture, circumstances, and needs)-at least over the duration of our project-produced stronger improvement in diabetes quality measures than a less structured and more open-ended approach.…”
Section: Discussionsupporting
confidence: 59%
“…Practices in the RAP arm received practice facilitation using the Reflective Adaptive Process change model based on complexity theory. 9,[24][25][26] The RAP approach focused on changing organizational functioning in order to improve diabetes care. The conceptual model underlying this approach assumes that improving organizational capacity to make and sustain change is fundamental in achieving practice improvements and implementing changes.…”
Section: Studymentioning
confidence: 99%
“…The ULTRA study was designed to test the effect of a quality improvement process on adherence to multiple chronic disease guidelines issued by the US Preventive Services Task Force and the American Diabetes Association, including those for diabetes care, and followed primary care practices in New Jersey and Pennsylvania for 2 years, collecting data at baseline and at 1-and 2-year followup assessments. 16,17 The quality improvement intervention focused on helping practices develop processes for refl ection and adaptation to change.…”
Section: Methodsmentioning
confidence: 99%
“…Our data collection methods have previously been described. 17 Briefl y, physician-owners or offi ce managers at participating practices reported various organizational characteristics including practice type, ownership structure, number of clinicians and other staff, number of years in business, estimates of insurance payer mix, and whether they used an EHR. In addition, fi eld researchers collected observational data documenting the type of medical records systems used in participating practices.…”
Section: Data Collectionmentioning
confidence: 99%
“…[25][26][27] Others have adopted more systemic approaches to change based on complexity science, including the reflective adaptive process (RAP). [28][29][30] Organizational culture has been shown to be associated with successful innovation and quality of care in medical practices.31-33 RAP focuses on enhancing practice capacity to make change by improving a practice's change culture, communication, problem solving, and organizational learning to lay the groundwork for an ongoing process of change and improvement.We undertook a cluster-randomized controlled trial, Enhancing Practice, Improving Care (EPIC), to compare the effectiveness of 3 approaches for implementing and sustaining Chronic Care Model-based systems to improve diabetes care: (1) practice facilitation using a RAP approach to stimulate reflective conversations and improve the practice's capacity to manage change, applying the change process to diabetes care; (2) practice facilitation using a CQI approach to implement quality improvement for diabetes to improve diabetes care; and (3) providing self-directed (SD) practices with information and resources about the Chronic Care Model and quality improvement to improve diabetes care, but without facilitation. Our hypotheses were that (1) the RAP approach would improve practice change culture to a greater and more sustained degree than the CQI or self-directed approaches; (2) the CQI approach would lead more quickly to improvement in diabetes performance measures than the RAP or SD approaches; and (3) the RAP approach would produce more sustained improvements in performance measures through positive impact on practice change and work cultures.…”
mentioning
confidence: 99%